2020
DOI: 10.3389/fonc.2020.00755
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Hotspot Mutation Analysis of Urinary Cell-Free DNA in Urothelial Bladder Cancer

Abstract: Recent studies showed the clinical utility of next-generation sequencing of urinary cell-free DNA (cfDNA) from patients with urothelial bladder cancer (UBC). In this study, we aimed to develop urinary cfDNA analysis by droplet digital PCR (ddPCR) as a high-throughput and rapid assay for UBC detection and prognosis. We analyzed urinary cfDNA of 202 samples from 2 cohorts. Test cohort was designed for investigating clinical utility of urinary cfDNA, and was composed of 74 samples from patients with UBC, and 52 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…These mutations are identified in both the normal tissues, which may be precancerous lesion, and the tumor samples of bladder cancer including various rare histological variants (micropapillary, plasmacytoid, adenocarcinoma, squamous cell carcinoma) [ 21 , 22 , 23 , 24 , 25 , 26 ]. These mutations can also be detected with ease in both the pellet and cell-free DNA from patient urine samples, promising application in urine-based disease detection and prediction of progression [ 27 , 28 , 29 , 30 ].…”
Section: Representative Genetic Mutations In Bladder Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…These mutations are identified in both the normal tissues, which may be precancerous lesion, and the tumor samples of bladder cancer including various rare histological variants (micropapillary, plasmacytoid, adenocarcinoma, squamous cell carcinoma) [ 21 , 22 , 23 , 24 , 25 , 26 ]. These mutations can also be detected with ease in both the pellet and cell-free DNA from patient urine samples, promising application in urine-based disease detection and prediction of progression [ 27 , 28 , 29 , 30 ].…”
Section: Representative Genetic Mutations In Bladder Cancermentioning
confidence: 99%
“…ERCC2 signature mutations were at higher levels in smokers than nonsmokers [ 30 ]. Fantoni F. et al reported molecular footprints of MIBCs in smoking and nonsmoking patients [ 57 ].…”
Section: Potential Effects Of Environmental Factors On Bladder Canmentioning
confidence: 99%
“…These findings are in line with an initial study from 2007 reporting the superiority of urinary cfDNA over cellDNA for the detection of genetic alterations of patients with urothelial cancer [ 78 , 79 ]. Applied to the detection of the TERT promoter mutations, two recent studies highlighted the potential of the marker in urinary cfDNA for the detection of BC [ 80 , 81 ]. Specifically, of 77 patients whose tumor cells carried the 228 G > A/T mutation, the same mutation was detected by ddPCR in urinary cfDNA of 71 individuals (92%) and the mutation was absent in cfDNA of 26 of 27 healthy patients (specificity of 96%).…”
Section: Urinary Tert Promoter Mutations: the Hmentioning
confidence: 99%
“…In combination with cytology, these mutations achieved a sensitivity of 78.6% and a specificity of 96.0% in diagnosis and staging of upper tract urothelial carcinoma [ 47 ]. In another study, these authors [ 48 ] evidenced that the diagnostic sensitivity of this strategy outperformed that of the combination of cytology and UroVysion, an FDA-approved assay to aid in BC diagnosis.…”
Section: Resultsmentioning
confidence: 99%